2009
DOI: 10.1016/j.brat.2009.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and cognitive expectancy of aversive outcome in avoidance conditioning

Abstract: a b s t r a c tFear conditioning studies have shown that social anxiety is associated with enhanced expectancy of aversive outcome. However, the relation between cognitive expectancy and social anxiety has never been tested in avoidance conditioning paradigms. We compared 48 low (LSA) and high socially anxious individuals (HSA) on subjective expectancy of aversive outcome during an avoidance conditioning task. Displays of neutral faces were coupled with an aversive outcome (US): a shout and a shock. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 36 publications
3
34
0
1
Order By: Relevance
“…These differences in uncertainty might explain why we observe selective learning for CS+2s but not for CS+1s. Indeed, research on expectancy biases of anxious populations has shown that these biases are especially pronounced under conditions of uncertainty (Calvo & Dolores Castillo, 2001;Chan & Lovibond, 1996;Ly & Roelofs, 2009 Whereas our data are generally in correspondence with the expectancy bias model of Davey (1992), our experiments did not include a replication of the resistance to instructed extinction effect (Hugdahl & Öhman, 1977;Hugdahl, 1978). This effect strongly favors the theory of a fear learning module because it shows that fear for fear-relevant CSs seems to be insensitive to cognitive interventions once it has been installed (Öhman & Mineka, 2001).…”
Section: Discussionsupporting
confidence: 51%
“…These differences in uncertainty might explain why we observe selective learning for CS+2s but not for CS+1s. Indeed, research on expectancy biases of anxious populations has shown that these biases are especially pronounced under conditions of uncertainty (Calvo & Dolores Castillo, 2001;Chan & Lovibond, 1996;Ly & Roelofs, 2009 Whereas our data are generally in correspondence with the expectancy bias model of Davey (1992), our experiments did not include a replication of the resistance to instructed extinction effect (Hugdahl & Öhman, 1977;Hugdahl, 1978). This effect strongly favors the theory of a fear learning module because it shows that fear for fear-relevant CSs seems to be insensitive to cognitive interventions once it has been installed (Öhman & Mineka, 2001).…”
Section: Discussionsupporting
confidence: 51%
“…Individuals with SAD reported heightened emotional reactions to both positive and negative social events (e.g., Gilboa-Schechtman et al, 2000). Experimental interpersonal manipulation studies consistently found that individuals with high social anxiety or SAD reported more intense, persistent negative affect in anticipation of, and following, various social challenges such as public speaking (e.g., Rapee and Lim, 1992; Ly and Roelofs, 2009), social ostracism (Oaten et al, 2008) and social success (Wallace and Alden, 1997) compared to individuals with low social anxiety.…”
Section: Integration Of Theoretical Approaches To Social Anxietymentioning
confidence: 99%
“…In this way, "avoidance interacts with anxiety through the mediating process of expectancy of the aversive outcome" (Lovibond, 2006, p. 126). Several laboratory studies have provided support for the key features of the expectancy model of avoidance learning (Declercq & De Houwer, 2008, 2009a, 2011Lovibond, Mitchell, Minard, Brady, & Menzies, 2009;Lovibond, Saunders, Weidemann, & Mitchell, 2008;Ly & Roelofs, 2009). Despite these advances, an important challenge remains in how to conceptualize avoidance that occurs not only in the presence of the CS but also in the presence of stimuli indirectly related to the CS or US.…”
Section: Introductionmentioning
confidence: 96%